Contexts of property in Europe : the social embeddedness of property rights in land in historical perspective - Congost, Rosa (2010)
The essays in this book tap the potential of the historical analysis of social contexts in which property rights are embedded - social relations, power and agency, political institutions, culture - to understand how landed resources are actually appropriated. This exploratory approach seeks both to take advantage of the existing theory of property rights, as it is applied by the institutionalist outlook on economic history, and to go beyond it by explicitly incorporating social processes and factors in the analysis of property institutions. With this common aim in mind, the book covers a wide variety of historical cases throughout space and time, from the late Middle Ages in the Czech lands and in Tuscany to the very recent de-collectivisation of the countryside in former socialist countries, which will contribute rich and grounded insights to the discussion of the topic and of its implications.